Implementation of Multicultural Education as an Effort to Build an Attitude of Tolerance among Students at Tanwirul Qulub Islamic Boarding School - Muharrom Dwiki Anom; Sauqi Futaqi; Siti Lathifatus Sun'iyah (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2026)
This study focuses on the implementation of multicultural education at the Tanwirul Qulub Islamic Boarding School in Lamongan and its contribution to fostering tolerance among students. Using a qualitative case study approach, data collection was conducted through observation, in-depth interviews, and documentation analysis. The results show that multicultural education at this Islamic boarding school is realized through various activities, both formal and informal. In the formal realm, implementation is seen in the study of yellow books, madrasah diniyah, and school education that emphasizes universal Islamic values. Meanwhile, in the informal realm, multicultural values are practiced through the students' daily activities such as roan (joint community service), deliberations, and the manaqib activities of Sheikh Abdul Qadir Jaelani, which involve broad community participation. Through these various activities, the Islamic boarding school strives to instill the values of tasamuh (tolerance), ukhuwah (brotherhood), and ta'awun (mutual assistance) that are internalized in the students' attitudes and behavior. Students are taught to live side by side without discrimination based on region of origin, social background, or cultural differences. Despite challenges such as a lack of formal understanding of the concept of multicultural education and limited learning media, its implementation has proven quite effective. Cross-cultural interactions among students are a crucial means of building harmony, solidarity, and mutual respect within the pesantren.